Artificial intelligence, digital capital, and epistemic domination on Twitter: A study of families affected by imprisonment. (January 2023) - Ugwudike, Pamela; Fleming, Jenny
Online Social Networking Sites (SNSs) and other Artificial Intelligence (AI) systems are transforming the epistemological foundations of justice systems and influencing knowledge production concerning criminal justice and its impact. This article focuses on a dimension of criminal justice which is the impact of imprisonment on families and seeks to unravel how knowledge about this problem is produced on SNSs. To this end, it draws on a study that explored conversational networks of key stakeholders on the SNS, Twitter. Building on insights from the study, the paper unravels interdependent sociotechnical dynamics that reproduce the offline marginality of affected families and operate as barriers to equitable knowledge production. Through its analysis of the dynamics, the paper provides new insights and advances the sparse criminological scholarship on the intersections of AI systems and the delivery of justice. It specifically highlights exclusionary epistemic processes that are fomented by the infrastructure of AI systems and the social contexts in which they are deployed.